THE EFFECT OF FERMENTED PAPAYA ( Carica papaya L) LEAVES IN RATION ON THE PERFORMANCE OF KAMPUNG CHICKENS (Gallus domesticus) - I M. Y., Prayoga; Puger, A.W.; Astawa, I P. A. (Jurnal Peternakan Tropika; Vol 9 No 3 (2021): Vol. 9 No. 3 Tahun 2021; September - December, 2021)
This study aims to determine the effect of fermented papaya leaves in the ration on the performance of kampung chickens. The design used was a completely randomized design (CRD) consisting of 4 treatments and 4 replications, each replication consisting of 3 kampung chickens. The treatments given were, P0 (rations without fermented papaya leaves), P1 (rations containing 10% fermented papaya leaves), P2 (rations containing 15% fermented papaya leaves), P3 (rations containing 20% ??fermented papaya leaves). The variables observed included ration consumption, initial body weight, final body weight, body weight gain, feed conversion ratio (FCR). Data were analyzed by analysis of variance, if there is a significant difference between treatments (P <0.05). ), then Duncan's multiple range test was carried out. The results showed that rations containing 10% fermented papaya leaves (P1), rations containing 15% fermented papaya leaves (P2), and rations containing 20% ??fermented papaya leaves (P3), were able to significantly increase (P<0.05) final body weight, weight gain and feed coverage ratio (FCR) but not significantly different (P> 0.05) in the consumption of the ration compared to the control treatment (P0). It can be concluded that up to 15% ??fermented papaya leaves can improve the performance.   Keywords: growth, free-range chicken, fermented papaya leaves